Letter to EditorsAre granular osmiophilic material deposits an epiphenomenon in CADASIL? - Erro, Roberto; Moccia, Marcello; Cervasio, Mariarosaria; Penco, Silvana; Caro, Marialaura Del Basso De; Barone, Paolo (Folia Neuropathologica, 2015)
Cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is caused by mutations in the NOTCH3 gene. Pathophysiologically, there seems to be multimerization of the extracellular domain of the protein with a possible gain of function on vascular smooth muscular cells. However, the mechanisms and determinants of NOTCH3 multimerization are not completely understood, and it is not completely elucidated whether NOTCH3 multimerization contributes to the appearance of granular osmiophilic material (GOM) deposits, which are the pathological hallmark of CADASIL. We recently reported a patient with parkinsonism and cognitive impairment and with evidence of diffuse white matter changes on imaging, carrying a NOTCH3 nonsense mutation in exon 3 (c.307C>T), and suggested that such a hypomorphic NOTCH3 mutation was likely to be pathogenic. We further pursued ultrastructural examination of skin vessels in our case, and here we report the results, wishing to make a comment on whether GOM deposits should be considered the pathological hallmark for a definitive diagnosis of CADASIL in those patients whose mutations are predicted in the production of hypomorphic protein products.